Cold restraint stress-induced gastric mucosal dysfunction - Role of nitric oxide - (:unkn) unknown (PLENUM PUBL CORP, 1996)
The objectives of this study were to determine the cold restraint stress-induced changes in gastric mucosal permeability and to assess whether nitric oxide synthesis inhibition affects gastric mucosal integrity after cold-restraint administration. Cold-restraint stress caused multiple gastric lesions in 90% of animals. The lesion index was found to be 3.87 +/- 0.97 mm, Gastric mucosal permeability to the [Cr-51]EDTA molecule was significantly elevated in the cold-restraint group compared to control. In order to evaluate the role of nitric oxide in cold restraint stress-induced gastropathy, L-arginine analog N-G-nitro-L-arginine methyl ester (L-NAME) was given as a bolus (10 mg/kg, intravenously) and infused at a rate of 2 mg/ml/hr for 2 hr after cold-restraint administration. L-NAME greatly exacerbated gastric mucosal dysfunction associated with cold-restraint stress, D-NAME, the biologically inactive enantiomer, did not enhance mucosal dysfunction, whereas L-arginine, the substrate for nitric oxide, reversed the effect of L-NAME. In an additional group of experiments, effects of cold-restraint stress and L-NAME on net transmucosal fluid flux as well as tissue myeloperoxidase activity (MPO) were assessed, Cold-restraint stress administration significantly reduced the absorptive capacity of stomach, whereas L-NAME treatment did not affect the stress-induced alterations on net fluid absorption. Furthermore, L-NAME treatment did not affect the cold restraint stress-induced changes in tissue MPO activity. Our results suggest that gastric barrier function is altered after cold-restraint stress and nitric oxide production is important in minimizing mucosal barrier dysfunction associated with cold-restraint stress administration, Our results also indicate that L-NAME-induced alterations on mucosal permeability are not related to net transmucosal fluid flux and tissue neutrophils.
Keywords: cold restraint; mucosal permeability; nitric oxide; LEUKOCYTE ADHESION; LESION FORMATION; RELAXING FACTOR; ACID-SECRETION; BLOOD-FLOW; RATS; INHIBITION; INJURY; PERMEABILITY; SUPEROXIDE